1998
DOI: 10.1046/j.1365-3024.1998.t01-1-00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the T cell epitopes of the Babesia bovis antigen 12D3: implications for vaccine design

Abstract: The Babesia bovis antigen 12D3 was analysed to identify potential T-cell epitopes. Two predictive algorithms identified 13 possible sites but there was minimal agreement between the different predictive methods. Experimental determination of the T-cell epitopes recognized by nine cattle was achieved using a panel of overlapping peptides which identified seven different epitopes, five of which were clustered together around residues 210-320 of the molecule. No T cell epitopes were located within the tightly dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…12D3 localized to the apical end of the merozoite and the cytoplasm of infected erythrocytes, suggesting that like RAP‐1, it is a secreted protein (62). Later studies showed that 12D3 contains several T cell epitopes recognized by 12D3‐immunized cattle (63), although our laboratory was consistently unable to stimulate recall CD4 + T cell responses with recombinant 12D3, using lymphocytes obtained from infected and recovered cattle that otherwise responded to B. bovis and specific antigens, such as RAP‐1 (Brown, unpublished observations). A truncated form of recombinant RAP‐1 fused to GST was reported to confer partial protection against challenge, determined as reduction in packed erythrocyte volumes (12).…”
Section: Strategies To Identify Protective Antigensmentioning
confidence: 94%
“…12D3 localized to the apical end of the merozoite and the cytoplasm of infected erythrocytes, suggesting that like RAP‐1, it is a secreted protein (62). Later studies showed that 12D3 contains several T cell epitopes recognized by 12D3‐immunized cattle (63), although our laboratory was consistently unable to stimulate recall CD4 + T cell responses with recombinant 12D3, using lymphocytes obtained from infected and recovered cattle that otherwise responded to B. bovis and specific antigens, such as RAP‐1 (Brown, unpublished observations). A truncated form of recombinant RAP‐1 fused to GST was reported to confer partial protection against challenge, determined as reduction in packed erythrocyte volumes (12).…”
Section: Strategies To Identify Protective Antigensmentioning
confidence: 94%
“…Leading candidate B. bovis antigens for vaccine development have included rhoptry-associated protein 1 (RAP-1), merozoite surface antigen 1 (MSA-1), 12D3, and spherical-body protein 1 (SBP1), formerly called Bv80 or Bb-1 (9,12,14,16,27,28,56,59). Mapping of CD4 ϩ T-cell epitopes on RAP-1, SBP-1, and 12D3 and characterization of the cytokine responses by antigen-specific Th cells were also carried out with the ultimate goal of constructing a multiepitope vaccine (14,16,43).…”
mentioning
confidence: 99%
“…Mapping of CD4 ϩ T-cell epitopes on RAP-1, SBP-1, and 12D3 and characterization of the cytokine responses by antigen-specific Th cells were also carried out with the ultimate goal of constructing a multiepitope vaccine (14,16,43).…”
mentioning
confidence: 99%
“…10,50 In Australia this work has all but been discontinued. The major limitations such as research funding, variations in immune responsiveness 75 and the need for repeat vaccinations mean that recombinant products cannot presently compete with the available live vaccine.…”
Section: The Futurementioning
confidence: 99%